Combination immunotherapy with prostate GVAX and ipilimumab: safety and toxicity. (June 2012) - Karan, Dev; Van Veldhuizen, Peter
Evaluation of: van den Eertwegh AJ, Versluis J, van den Berg HP et al. Combined immunotherapy with granulocyte-macrophage colony-stimulating factor-transduced allogeneic prostate cancer cells and ipilimumab in patients with metastatic castration-resistant prostate cancer: a Phase 1 dose-escalation trial. Lancet Oncol. 13(5), 509–517 (2012). A significant interest in the development of therapeutic cancer vaccines over the last decade has led to an improvement in overall survival of cancer patients in several clinical trials. As a result, two active immunotherapy agents, sipuleucel-T and ipilimumab, have been approved by the US FDA for the treatment of prostate cancer and melanoma, respectively. GVAX ® cellular vaccine (Cell Genesysis, Inc., CA, USA) is another active immunotherapy agent targeting prostate cancer and it has been well studied in various clinical trials. The current publication, by van den Eertwegh et al., demonstrated a combination of two active immunotherapy approaches, using GVAX and ipilimumab for the treatment of metastatic castration-resistant prostate cancer. While GVAX is designed to amplify the antitumor response specific to prostate cancer cells, ipilimumab contributes to T-cell activation. Thus, the authors presented the possibility of augmenting antitumor T-cell activity in two different ways. They successfully demonstrated a tolerable dose and safety profile of ipilimumab in combination with GVAX for patients with metastatic castration-resistant prostate cancer. However, further studies of such immunotherapy combinations and detailed analysis of their immunological effects are needed to observe clinical benefit.